Associations of perioperative variables with the 30-day risk of stroke or death in carotid endarterectomy for symptomatic carotid stenosis - Knappich, Christoph; Kuehnl, Andreas; Haller, Bernhard; Salvermoser, Michael; Algra, Ale; Becquemin, Jean-Pierre; Bonati, Leo H.; Bulbulia, Richard; Calvet, David; Fraedrich, Gustav; Gregson, John; Halliday, Alison; et al. (Stroke, 2019)
Background and Purpose—This analysis was performed to assess the association between perioperative and clinical variables and the 30-day risk of stroke or death after carotid endarterectomy for symptomatic carotid stenosis.Methods—Individual patient-level data from the 5 largest randomized controlled carotid trials were pooled in the Carotid Stenosis Trialists’ Collaboration database. A total of 4181 patients who received carotid endarterectomy for symptomatic stenosis per protocol were included. Determinants of outcome included carotid endarterectomy technique, type of anesthesia, intraoperative neurophysiological monitoring, shunting, antiplatelet medication, and clinical variables. Stroke or death within 30 days after carotid endarterectomy was the primary outcome. Adjusted risk ratios (aRRs) were estimated in multilevel multivariable analyses using a Poisson regression model.Results—Mean age was 69.5±9.2 years (70.7% men). The 30-day stroke or death rate was 4.3%. In the multivariable regression analysis, local anesthesia was associated with a lower primary outcome rate (versus general anesthesia; aRR, 0.70 [95% CI, 0.50-0.99]). Shunting (aRR, 1.43 [95% CI, 1.05-1.95]), a contralateral high-grade carotid stenosis or occlusion (aRR, 1.58 [95% CI, 1.02-2.47]), and a more severe neurological deficit (mRS, 3-5 versus 0-2: aRR, 2.51 [95% CI, 1.30-4.83]) were associated with higher primary outcome rates. None of the other characteristics were significantly associated with the perioperative stroke or death risk.Conclusions—The current results indicate lower perioperative stroke or death rates in patients operated upon under local anesthesia, whereas a more severe neurological deficit and a contralateral high-grade carotid stenosis or occlusion were identified as potential risk factors. Despite a possible selection bias and patients not having been randomized, these findings might be useful to guide surgeons and anesthetists when treating patients with symptomatic carotid disease.
Gesehen am 16.04.2020